LEADING FACTORS OF MORPHOLITHOGENESIS IN THE LATE QUATERNARY HISTORY OF WEST SIBERIA - Zol'nikov I.D.; Gus'kov S.A.; Orlova L.A.; Kuz'min Ya.V.; Levchuk L.K. (My University, 2003)
Some stratigrapho-paleogeographic discrepancies have been removed from the interpretation of spatial-temporal relationships between leading factors of morpholithogenesis in the Late Pleistocene of West Siberia. New data obtained from mammoth remains indicate that there was no dam basin on the West Siberian Plain in Sartan time. A hypothesis has been formulated that the Karga marine deposits occur in overdeepened lows, tens of meters below the paleolevel of the ocean, which formed when the dammed waters broke the ice dam to run northward. This refines the configuration of the Karga sea transgression whose deposits are mapped on the north of West Siberia in accordance with a recent stratigraphic scheme. The Late Pleistocene and Holocene of West Siberia include relatively long stages of stable and metastable ecogeologic settings alternating with short epochs of drastically contrasting transformations of paleolandscapes.
Keywords: Sartan horizon; ice-dammed basin; Karga sea transgression; radiocarbon method; paleogeography; West Siberia; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен